Heat acclimation with controlled heart rate: Influence of hydration status - Travers, G.; Nichols, D.; Riding, N.; González-Alonso, J.; Périard, J. D. (Medicine & Science in Sports & Exercise, 2020)
Purpose: This study aimed to characterize the adaptive responses to heat acclimation (HA) with controlled heart rate (HR) and determine whether hydration strategy alters adaptations. The influence of HA on maximal oxygen uptake (VO2max) in cool conditions and self-paced exercise in the heat was also determined.